Ecology, Politics, and Aestheticism in Amitav Ghosh’s The Hungry Tide - Parampil, Anjali Joshi; Singh, Jai (Mindscape: A Journal of English & Cultural Studies, 2025)
Ecocriticism is a broad field which is located at the intersection of ecology, politics, and aestheticism. This research paper applies the theoretical framework of ecocriticism to analyze Amitav Ghosh’s The Hungry Tide, an important work of ecofiction wherein the author brings in several questions involving man-animal conflicts, conservationism, climate changes, and endangerment of species as well as the location of women in the nature. Ghosh’s representation of environmental issues is completely different from Romantic poets because his representation of nature is situated at the intersection of ecology, politics, and aestheticism. Unlike the refuge in nature that the Romantic poets often implied when it came to going ‘back to nature,’ Ghosh’s aestheticism is completely different. The struggle to protect environment on the one hand and the complicity of various organizations with capitalism and capitalism sponsored government agencies is foregrounded by Ghosh in the text. The paper also foregrounds the sexualisation of nature in the form of a woman’s body. This aesthetics of literature wherein women are equated with nature and the description of one becomes the description of the other is questioned by using the arguments put forward by Val Plumwood.